Early Cytokine Response to Infection with Pathogenic vs Non-Pathogenic Organisms in a Mouse Model of Endodontic Infection - Matsui, Aritsune (PLoS One, 2015)
Using the subcutaneous chamber model of infection, we showed previously that a mixture of four endodontic pathogens (EP: P. intermedia, F. nucleatum, S. intermedius and P. micra) are able to persist without clearance for up to seven days, while a non-pathogenic oral species, S. mitis, was substantially cleared in this time. Here we have compared the cytokine response inside the chambers against these microorganisms. A majority of cytokines tested (17/24) showed different patterns of expression. Several cytokines had a peak of expression at 2 h after infection in response to the EP, while none showed this pattern in S. mitis infections. Chemokines were uniformly present at similar or higher levels in response to S. mitis, with redundant expression of CXCR2 ligands, while several growth/survival factors were present at higher levels in EP infections. Protease activity expressed by EP may be responsible for the lower levels of some chemokines. T-cell associated cytokines were in general expressed at extremely low levels, and did not differ between the two infections. The inflammatory markers IL-6, IL-1α and IL1-β were expressed at similar levels in both infections at early times, while TNFα was preferentially present in S. mitis infections. In EP infected chambers, reciprocal changes in levels of IL-6 and IL-1α were observed at later times suggesting a switch in the inflammatory response. Analysis of the cytokine response to infection with the individual species from the EP mix suggests that P. intermedia drives this inflammatory switch. Together these results show a surprising level of divergence of the host response to pathogenic and non-pathogenic organisms associated with oral infections, and supports a dominant effect of P. intermedia in polymicrobial endodontic infections.